Metode Akra-Bazzi Sebagai Generalisasi Metode Master Dalam Menyelesaikan Relasi Rekurensi - Muchammad Abrori (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2013)
Rekurensi relation is an equation that relates the elements of a sequence. One of the benefits of the rekurensi relation can be used to calculate the running time/finish of an algorithm. Some algorithms use approach devide-and-conquer in resolving a problem. Rekurensi relations with the approach of the devide and conquer can be solved by several methods. This research aims to know the Akra-Bazzi Method as an extension Method of the Master. This research began with the dissected the concept pertaining to the Relation Rekurensi, methods for resolving Relationship Rekurensi, and lastly about methods of AkraBazzi. Note that Akra-Bazzi Method can solve a rekurensi devide-and-conquer with shorter calculation.